2011
DOI: 10.1007/s13317-011-0025-9
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of a human thyroid-stimulating monoclonal autoantibody (M22) and a human thyroid-blocking autoantibody (K1-70)

Abstract: PurposeTo study in vivo effects of the human monoclonal TSH receptor (TSHR) autoantibodies M22 (stimulating type) and K1-70 (blocking type) on thyroid hormone levels in rats.MethodsSerum levels of total T4, free T4, M22 and K1-70 were measured following intramuscular injection of M22 IgG (2–4 μg/animal), K1-70 IgG (10–200 μg/animal) or both into rats. Thyroid pathology was assessed in M22-injected rats.ResultsSerum levels of total T4 and free T4 increased in a dose-dependent manner following injection of M22 I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 24 publications
(41 reference statements)
0
42
0
1
Order By: Relevance
“…The monoclonal TSAbs derived from experimental models of Graves' disease have been shown to be pathogenic in vivo, confirming their role in disease pathogenesis (8)(9)(10). Importantly, human monoclonal TSAbs from patients with Graves' disease have also been derived, providing detail into their molecular and biochemical properties, and pathogenicity in vivo (11)(12)(13). A major advance has been the delineation of the atomic structures of immune complex of human monoclonal TSAb, M22 and human monoclonal TSBAb, and K1-70 with human TSHR A-subunit (14)(15)(16).…”
mentioning
confidence: 72%
“…The monoclonal TSAbs derived from experimental models of Graves' disease have been shown to be pathogenic in vivo, confirming their role in disease pathogenesis (8)(9)(10). Importantly, human monoclonal TSAbs from patients with Graves' disease have also been derived, providing detail into their molecular and biochemical properties, and pathogenicity in vivo (11)(12)(13). A major advance has been the delineation of the atomic structures of immune complex of human monoclonal TSAb, M22 and human monoclonal TSBAb, and K1-70 with human TSHR A-subunit (14)(15)(16).…”
mentioning
confidence: 72%
“…From the maximum 145 mg HED from the rat toxicology study data the maximum systemic exposure to K1-70 ™ for the first in human study was determined at C max of 0.031 mg/mL. Furthermore, a starting dose of K1-70 ™ for human studies was calculated based upon Food and Drug Administration (FDA) guidance [37] using in vivo effects of IM injections of K1-70 ™ on thyroid hormone production in rats made hyperthyroid with M22 ™ [17]. Dose dependent suppression of thyroid activity was observed following IM doses of 50 to 200 µg K1-70 ™ , with no significant effects observed at doses of 4 and 10 µg K1-70 ™ .…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary in vivo studies have demonstrated that administration of K1-70 ™ causes biochemical hypothyroidism in untreated rats and in rats made hyperthyroid with the thyroid stimulating human monoclonal autoantibody M22 [16][17][18]. The decreases in thyroid hormone levels post K1-70 ™ were associated with thyroid follicular Open Access Furmaniak et al Autoimmun Highlights (2019) 10:11 cell atrophy and enlarged thyroid follicles filled with colloid, consistent with hypothyroidism [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Among other small molecules are those that can block thyroid-stimulating immunoglobulin actions in vitro and can also exert inhibition in vivo in small animal models (84,85). Besides small molecules, several anti-TSHR antibodies have shown receptor-blocking activities (44,86,87). Included among these are inverse agonists, which inhibit constitutive TSHR activities (88).…”
Section: Tshr As a Therapeutic Target In Gdmentioning
confidence: 99%
“…These include IL-1β, IL-6 and TNF-α (40,41,42). They can undergo differentiation into adipocytes, myofibroblasts, chondrocytes and osteoblasts, depending on molecular environment surrounding them within tissues (43,44). Several factors have been shown to influence fibrocyte differentiation; Th1 cytokines and lumican enhance while Th2 cytokines (45,46), Slit2 (47) and serum amyloid P (48) inhibit this process.…”
Section: Introductionmentioning
confidence: 99%